(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kharkova E. D. Trends and prospects of transforming pre-school education in the modern educational environment in Ukraine. The paper considers the problem of transformation of pre-school education in the modern educational environment of Ukraine, called factors leading pre-school education, have provided separation of pre-school education.